2021
DOI: 10.14245/ns.2040402.201
|View full text |Cite
|
Sign up to set email alerts
|

Retro-Odontoid Pseudotumor Formation in the Context of Various Acquired and Congenital Pathologies of the Craniovertebral Junction and Surgical Techniques

Abstract: Retro-odontoid pseudotumor formation consists of an abnormal growth of granulation tissue typically posterior to the odontoid process, resulting as a manifestation of atlantoaxial instability. This instability can occur as a result of conditions ranging from severe mechanical trauma to metabolic disease or autoimmune conditions such as rheumatoid arthritis. A pseudotumor may impinge on the spinal nerves or even the spinal cord and brainstem, manifesting symptoms from severe neck pain to cervicomedullary compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…It has been well reported by many researchers that the retro-odontoid mass tissue disappeared after fixation of the CVJ. 14,17,18,25 Chang et al 17 observed that the TA decreased immediately after the surgery and continued to decrease until 2 years after surgery. In this study, the ΔTA was 1.18 cm 2 in patients who had combined anterior and posterior decompression surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well reported by many researchers that the retro-odontoid mass tissue disappeared after fixation of the CVJ. 14,17,18,25 Chang et al 17 observed that the TA decreased immediately after the surgery and continued to decrease until 2 years after surgery. In this study, the ΔTA was 1.18 cm 2 in patients who had combined anterior and posterior decompression surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Even if conservative therapy is indicated in most cases of CDS, surgery is also indicated in a few cases ( 27 ). Fiani et al ( 4 ) concluded that occipital–cervical fusion “is indicated in cases where the panni impinge on the medulla and the upper cervical cord” and that the “goal in occipital surgical fusion is to prevent further progression of the pseudotumor and improve neurological outcomes.” Furthermore, they concluded that “neurological improvements are often noted in patients as soon as 1 week after surgery and complete resolution of the pseudotumor can be visualized on imaging within 1 year of surgical repair.”…”
Section: Discussionmentioning
confidence: 99%
“…Retro-odontoid pannus may develop in the spinal canal ( 4 ), may cause compression of the brainstem, may result in quadriplegia, or may even lead to sudden death in rare cases ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A non-neoplastic soft tissue mass posterior to the dens is termed a retrodental or retro-odontoid mass (R-OM); in other studies, it was also referred to as a retro-odontoid or periodontoid pseudotumor 5 , 10 , 11 . R-OMs are often observed in patients with rheumatoid arthritis, congenital anomalies, os odontoideum, degenerative conditions, or trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier techniques were often followed by increased complications and failure rates 8 , while modern fixation materials and constructs have resulted in better outcomes. Currently, screw-based constructs provide rigid, short-segment stabilization-which is crucial in achieving successful fusion-thereby preventing aggravation of neurologic morbidity and myelopathy 9 .A non-neoplastic soft tissue mass posterior to the dens is termed a retrodental or retro-odontoid mass (R-OM); in other studies, it was also referred to as a retro-odontoid or periodontoid pseudotumor 5,10,11 . R-OMs are often observed in patients with rheumatoid arthritis, congenital anomalies, os odontoideum, degenerative conditions, or trauma.…”
mentioning
confidence: 99%